2015
DOI: 10.3126/kumj.v12i4.13736
|View full text |Cite
|
Sign up to set email alerts
|

Rare Presentation of Chorioadenoma Destruens as Acute Haemoperitoneum Mimicking Ruptured Ectopic Pregnancy

Abstract: Gestational trophoblastic neoplasms (GTN) are proliferative degenerative disorders of placental elements and include complete or partial mole (90%), invasivemole (5-8%), choriocarcinoma (1-2%) and placental site tumor (1-2%). Chorioadenoma destruens is a trophoblastic tumor, characterized by myometrial invasion through direct extension or via venous channels. We present a case of invasive mole eroding uterus and uterine vasculature, causing sudden rupture of uterus with massive haemoperitoneum mimicking ectopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Ectopic pregnancy is considered to be a great mimic in gynaecology [3] and chronic ectopic pregnancy poses a challenge because of its subtle symptoms and wide range of clinical presentation. A rare case report by Sinha M. et al describes a case of chorioadenoma destruens mimicking ruptured ectopic pregnancy [4]. A case report by Sakamoto Y et al reported gestational choriocarcinoma with uterine serosal metastasis mimicking ruptured ectopic pregnancy [5].…”
Section: Resultsmentioning
confidence: 99%
“…Ectopic pregnancy is considered to be a great mimic in gynaecology [3] and chronic ectopic pregnancy poses a challenge because of its subtle symptoms and wide range of clinical presentation. A rare case report by Sinha M. et al describes a case of chorioadenoma destruens mimicking ruptured ectopic pregnancy [4]. A case report by Sakamoto Y et al reported gestational choriocarcinoma with uterine serosal metastasis mimicking ruptured ectopic pregnancy [5].…”
Section: Resultsmentioning
confidence: 99%
“…Among 78 patients with GTN in the study by Xiaoyu Wang who achieved fertility-preserving surgery, only 5 patients underwent surgery due to suspected uterine rupture [ 7 ]. There have been several previous reports of cases of uterine perforation by an invasive mole, all of which were managed with abdominal hysterectomy [ 13 ]. To our knowledge, invasive mole perforation with active bleeding management by fertility-preserving surgery without hysterectomy is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic pregnancy is considered to be a great mimic in gynecology (3) and chronic ectopic pregnancy poses a challenge because of its subtle symptoms and wide range of clinical presentation. A rare case report by Sinha et al (4) describe a case of chorioadenoma destruens mimicking ruptured ectopic pregnancy. A case report by Sakamoto et al (5) reported gestational choriocarcinoma with uterine serosal metastasis mimicking ruptured ectopic pregnancy.…”
Section: Answermentioning
confidence: 99%